Bat diversity along an altitudinal gradient in the Itabapoana drainage basin, Espírito Santo state, Brazil - Vinicius Chagas Lopes; Rodrigo Martins Lemes; Atilla Colombo Ferreguetti; Sergio Barbiero Lage; Rodrigo da Silva Cipriano; Kauê Freire de Paula (Biotemas)
Among all the mammal species that occur along every montane altitudinal gradient in southeastern Brazil (i.e. Atlantic Forest), bats are an excellent model for analysis, because they are abundant, and all trophic guilds are represented within the taxon. In mountain chains around the world, bat communities may present two patterns of species richness and diversity: 1) progressive decline in species richness and diversity as the altitude increase or 2) a peak of richness and diversity in intermediate altitudinal level. In this context, we aimed to survey the bat species occurring in the Atlantic Forest remnants located in the Itabapoana drainage basin (IDB) and to verify how altitude affects bat capture rates. We used mist-nets to capture bats, which were set up at ground level, totaling 1,500 m2/ha of sampling effort for each location. The IDB has a diverse assemblage of species (26 species), representing 44% of the bat species of Espírito Santo. Our study showed that there is variation in bat capture rates and species richness, with a turnover of some species along the altitudinal gradient in the IDB. Changes in habitat heterogeneity along the elevation gradient are probably one of the strong ecological factors affecting these assemblage parameters. Furthermore, the data from this study allows the expansion of knowledge of the bat species occurring in the region of the IDB. The diversity of species found, together with the occurrence of rare, threatened, and data deficient species highlights the importance of the region for conservation to understand the species distribution patterns.